Evolution of Stress Rupture Property for K439B Superalloy During Long-Term Thermal Exposure at 800 °C - Yidong Wu; Xinghai Qu; Lei Gao; Chaoqian Song; Zhao Dong; Jingyang Chen; Xidong Hui (Metals)
The K439B superalloy is widely utilized in aeroengine components due to its superior weldability and mechanical performance. Given that the hot-end components of aeroengines typically operate at high temperatures for extended periods, even up to 10,000 h, it is essential to investigate the stress rupture properties and deformation mechanisms of K439B alloy after prolonged thermal exposure. In this work, thermal exposure at 800 °C for 6000, 8000, and 10,000 h was conducted for the K439B superalloy. Unlike the samples with aging times less than 6000 h, for the samples aged between 6000 and 10,000 h, the stress rupture life at 815 °C/379 MPa decreased slowly, from 47.3 to 39.1 h. Creep cracks typically originate at metal carbides (MC type) and subsequently propagate along grain boundaries. Notably, the creep deformation mechanism shifts under varying aging conditions. After 6000 h of aging, the deformation mechanism is primarily governed by Orowan bypassing and isolated stacking fault shearing. As the aging period increases further, the γ′ precipitates progressively coarsen, and isolated stacking faults become more prevalent, ultimately reducing the creep resistance of the alloy.